Generation of novel oncolytic vaccinia virus with improved intravenous efficacy through protection against complement-mediated lysis and evasion of neutralization by vaccinia virus-specific antibodies - Dong-Sup Lee; Mi-Ju Park; Namhee Lee; Yun-Hui Jeon; Jiyoon Yoo; Suk-kyung Shin; Songyi Lee; Byung-Jin Jung; Yun-Kyoung Hong; Keunhee Oh (Journal for ImmunoTherapy of Cancer)
Background Oncolytic virus immunotherapy has revolutionized cancer immunotherapy by efficiently inducing both oncolysis and systemic immune activation. Locoregional administration has been used for oncolytic virus therapy, but its applications to deep-seated cancers have been limited. Although systemic delivery of the oncolytic virus would maximize viral immunotherapy’s potential, this remains a hurdle due to the rapid removal of the administered virus by the complement and innate immune system. Infected cells produce some vaccinia viruses as extracellular enveloped virions, which evade complement attack and achieve longer survival by expressing host complement regulatory proteins (CRPs) on the host-derived envelope. Here, we generated SJ-600 series oncolytic vaccinia viruses that can mimic complement-resistant extracellular enveloped virions by incorporating human CRP CD55 on the intracellular mature virion (IMV) membrane.Methods The N-terminus of the human CD55 protein was fused to the transmembrane domains of the six type I membrane proteins of the IMV; the resulting recombinant viruses were named SJ-600 series viruses. The SJ-600 series viruses also expressed human granulocyte-macrophage colony-stimulating factor (GM-CSF) to activate dendritic cells. The viral thymidine kinase (J2R) gene was replaced by genes encoding the CD55 fusion proteins and GM-CSF.Results SJ-600 series viruses expressing human CD55 on the IMV membrane showed resistance to serum virus neutralization. SJ-607 virus, which showed the highest CD55 expression and the highest resistance to serum complement-mediated lysis, exhibited superior anticancer activity in three human cancer xenograft models, compared with the control Pexa-Vec (JX-594) virus, after single-dose intravenous administration. The SJ-607 virus administration elicited neutralizing antibody formation in two immunocompetent mouse strains like the control JX-594 virus. Remarkably, we found that the SJ-607 virus evades neutralization by vaccinia virus-specific antibodies.Conclusion Our new oncolytic vaccinia virus platform, which expresses human CD55 protein on its membrane, prolonged viral survival by protecting against complement-mediated lysis and by evading neutralization by vaccinia virus-specific antibodies; this may provide a continuous antitumor efficacy until a complete remission has been achieved. Such a platform may expand the target cancer profile to include deep-seated cancers and widespread metastatic cancers.